A Comparative Study of the Meaning of Life Between the Potential Elderly and the Abandoned Elderly in Greater Bandung - Husna, Dinda Novita Nurul; Muthi Annisa, Nida; Firdasannah, Astri (Communication in Research and Publications (CRP), 2025)
The elderly should be able to accept the changes however, according to Permensos No. 19 of 2012, the elderly grouped consisting of potential elderly and abandoned elderly are faced two different problems. The purpose of this study is to obtain a comparative picture of the dynamics of the meaning of life between potential elderly and abandoned elderly in Greater Bandung. The subjects of this study are four people consisting of two elderly from each type. This study used qualitative method, case study approach, with purposive sampling through interviews, observations, and documentation. The validity test used triangulation with the reliability test used dependability. The results of this study show that the two elderly have a meaningful life, the potential elderly are superior in the theme of freedom of will and meaning of life, while the abandoned elderly are superior in the theme of desire to live a meaningful life and expressing emotions.